Laser-welded fused silica substrates using a luminescent fresnoite-based sealant. (June 2016) - de Pablos-Martin, A.; Benndorf, G.; Tismer, S.; Mittag, M.; Cismak, A.; Lorenz, M.; Grundmann, M.; Höche, Th.
Abstract: The laser welding of two fused silica substrates using a fresnoitic glass thin film as a sealant by irradiation with a ns laser is studied. Two different laser parameter sets were compared in terms of bond quality, which include two different laser beam trajectories: linear and wobble (circular) trajectory. The composition of the glass sealant changes with the course of the laser welding, incorporating silica from the substrates. After joining, the bonded samples were exposed to UV light and a very intense emission in the blue spectral range is observed by naked eye, which is due to the crystallization of the fresnoite glass upon the laser irradiation. EDX analysis confirms the crystallization of fresnoite, together with a great enrichment in silica. The formation of a eutectic between both is very plausible. Bond quality and bond strength were evaluated by scanning acoustic microscopy (SAM) and tensile test, which results in a tensile stress of 7 MPa. Highlights: Two fused silica substrates were laser-bonded through a fresnoitic glass thin film. Two different laser beam trajectories and laser parameters were compared. The bonded sample exhibit blue luminescence under UV excitation. Fresnoite crystallizes upon laser irradiation.